2009
DOI: 10.1177/039463200902200405
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Map Kinases Inhibits Microglial Activation and Attenuates Neuronal Cell Death Induced by α-Synuclein Protofibrils

Abstract: The first two authors contributed equally to this work u-Synucleln (a-Syn) accounts, as a major component ofLewy bodies (LB), for the filamentous deposits in many cases of neurodegenerative diseases. Yet, little is known about the molecular mechanisms of neuronal loss in these diseases. The correlation between a-Syn oligomerization/aggregation and pathologies raises the key question of which molecular form of a-Syn (i.e. monomeric u-Syn, protofibrils or mature fibrils) represents the damage-inducing culprit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…The kinases and pathways involved in pathogenic αsyn phosphorylation have yet to be elucidated however studies have linked CK2, calcineurin, and p38 MAPK to cellular stress, PD, and αsyn 51-56 . Follow up screens of additional kinase inhibitors eliminated calcineurin, src family kinase, FGF-1R TK, and CK2 families of inhibitors as having activity in our assay, but suggested p38 MAPK inhibitors as putative targets for αsyn oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…The kinases and pathways involved in pathogenic αsyn phosphorylation have yet to be elucidated however studies have linked CK2, calcineurin, and p38 MAPK to cellular stress, PD, and αsyn 51-56 . Follow up screens of additional kinase inhibitors eliminated calcineurin, src family kinase, FGF-1R TK, and CK2 families of inhibitors as having activity in our assay, but suggested p38 MAPK inhibitors as putative targets for αsyn oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…The multitarget properties of CNI-1493 were further corroborated through differential effects of CNI-1493 and C1213 on the CRND8 mouse model. While CNI-1493 massively reduced Aβ plaque number and volume (14), the administration of C1213 merely reduced plaque volume at a statistically significant level. This difference suggests that microglial modulation through CNI-1493 is required for reduction of the plaque number.…”
Section: Disclosurementioning
confidence: 83%
“…Neuronal cell death induced by stereotactic injection of α-synuclein protofibrils in the rat substantia nigra could be markedly attenuated by intraperitoneal injection of CNI-1493 (14). Our group has previously shown that the MAPK inhibitor CNI-1493 can ameliorate the pathophysiology in TgCRND8 mice, a murine AD model that overexpresses human amyloid precursor protein (APP).…”
mentioning
confidence: 99%
“…Here, progressive degeneration of dopaminergic neurons in the substantia nigra and a subsequent reduction of DA levels in the striatum are caused by various mechanisms including inflammation (Brundin et al, 2008). Microglia substantially contribute to PD likely due to the accumulation of a-synuclein, which promotes proinflammatory signalling in these cells (Wilms et al, 2009). Loss of DA might thus induce a vicious cycle, progressively enhancing death of dopaminergic neurons.…”
Section: Dopaminementioning
confidence: 99%